Designing a Novel Hybrid Fuzzy GWO PID Load-Frequency Controller for a complicated Large-Scale Four-Area interconnected Power Grid with RES and SMES - Nguyen, Ngoc-Khoat; Doan, Diem-Vuong (Engineering, Technology & Applied Science Research, 2025)
Stable grid frequency control in modern interconnected power systems is increasingly challenging, especially with the increasing integration of Renewable Energy Sources (RES). This study solves the Load Frequency Control (LFC) problem in a complex four-area reheat turbine power system incorporating photovoltaic generation together with nonlinear characteristics, i.e., Governor Dead Band (GDB) and Generation Rate Constraints (GRC), and a Superconducting Magnetic Energy Storage (SMES) device. A novel hybrid controller, Fuzzy GWO PID, is proposed that combines the adaptability of fuzzy logic, the global search efficiency of the Grey Wolf Optimizer (GWO), and the precise regulation of a conventional Proportional-Integral-Derivative (PID) controller. The controller performance is benchmarked against a fractional-order PIλD and a GWO-optimized PID controller, aiming to minimize frequency deviations and improve dynamic stability under stochastic load variations and intermittent renewable energy fluctuations. Simulation results over various cases of load changes demonstrate that the proposed hybrid Fuzzy GWO PID controller outperforms the PIλD and GWO PID controllers. This type of novel LFC controller achieves much better control performances such as faster settling times, reduced overshoot, and improved dynamic response. This work obviously intends to highlight the effectiveness of integrating fuzzy logic with metaheuristic optimization for robust LFC in modern power grids with high renewable penetration.